Primary prevention of Chlamydia trachomatis infection in young women: impact of an informational video in a Swiss gynaecology emergency department (Swiss Medical Weekly, 2025)
OBJECTIVES: The primary objective was to measure the impact of passive exposure to an educational video about Chlamydia trachomatis infection shown in a gynaecology department waiting room on young women’s knowledge on the subject. The secondary objective was to explore the participants’ interest in improving their knowledge of Chlamydia trachomatis and their opinions on receiving this information during a consultation in the emergency room.METHODS: A prospective, interventional, controlled, non-randomised study. Participants were recruited between January and June 2022. 120 women aged 15–35 years were included. The intervention consisted of passive exposure to a 2-minute cartoon presenting basic foundational points of Chlamydia trachomatis displayed in the waiting room. The control group was not exposed to the video. After the intervention, an in-person knowledge interview was performed with each participant.MAIN OUTCOME MEASURES: The main outcome measures were the knowledge scores obtained in the interviews with the exposed and control groups.RESULTS: Both groups were similar regarding sociodemographic variables. The average knowledge scores from the interview were similar in the two groups. Video exposure was not associated with diminution of lower scores. Participants’ baseline knowledge was higher than expected on the basis of a literature review.CONCLUSION: The passive learning intervention described in this study did not improve the participants’ knowledge about Chlamydia trachomatis. During the one-to-one interview, participants were keen to receive information about Chlamydia trachomatis but the quantitative results show that the short video in the waiting room had no impact on their knowledge. Future studies should focus on pre-assessed, randomised, one-to-one or small-group active interventions.